STATE CONTROL AND SUPERVISION IN THE FIELD OF CONSUMER PROTECTION - DEMIDCHUK, LUDMILA; SAPOZHNIK, DMYTRO (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article examines the administrative and legal issues of control and supervision in the area of consumer protection over the quality and safety of consumer goods and services in the context of modern reforms of public authorities. The purpose of the study is to establish the correlation between the concepts of supervision and control over compliance with legislation in the field of consumer protection as legal categories. The author examines the main controlling powers of public authorities and local self-government bodies in the field of consumer protection. The author provides provisions on measures aimed at strengthening the interaction of structural units of the State Service of Ukraine on Food Safety and Consumer Protection with local self-government bodies. It is shown that the concepts of "control" and "supervision" are widely used both in theory and in legislative activities, but so far these concepts have not received clear definitions which would make it clear how the functions they contain relate to each other. In exercising control and supervision powers, the state, represented by authorised bodies, suppresses violations of legislation in the field of consumer protection, quality and safety of food products, conducts preliminary, current and subsequent control, while applying administrative measures to the persons who have committed such offences. It is stated that recently the system of state controlling bodies has been subject to justified criticism both by the professionals exercising such control and by the "controlled" objects. The authorities exercising state control in the field of consumer protection, as well as over the quality and safety of consumer goods, are no exception. It is noted that the controlling apparatus of the authorities has grown significantly in recent years, and this numerical growth is not always justified. Often, controlling authorities duplicate each other. There are no established contacts and coordination of activities of various controlling authorities. These shortcomings prevent the use of potential opportunities for improving economic governance inherent in control. The article proposes measures to improve legislation in terms of separation of control and supervision functions in public administration based on the specified criteria, regulation of control and supervision procedures, which will allow limiting the legal framework of control and supervision activities of the State. This may help to resolve a number of problems in the public administration system, in particular, reduce the level of corruption and excessive administrative pressure in the field of business.